A new species of the genus Xistra (Orthoptera: Tetrigoidea: Metrodorinae) with comments on the characters of mitochondrial genome - Bai, Qiu-Xia; Long, Min; Deng, Wei-An (Zootaxa, 2024)
A new species from Jiangxi Province of China, Xistra zhengi Deng, sp. nov. is described and illustrated. Meanwhile, the complete mitochondrical genome of the new species was determined and annotated. It has the typical invertebrate mitochondrial gene arrangement, the size of the sequenced mitogenomes is 18148 bp. The constructed phylogenetic tree showed that the new species was placed in Metrodorinae, and formed a separate clade from other species of Metrodorinae.